2017
DOI: 10.1016/j.jcp.2017.02.039
|View full text |Cite
|
Sign up to set email alerts
|

On conservation laws of Navier–Stokes Galerkin discretizations

Abstract: We study conservation properties of Galerkin methods for the incompressible NavierStokes equations, without the divergence constraint strongly enforced. In typical discretizations such as the mixed finite element method, the conservation of mass is enforced only weakly, and this leads to discrete solutions which may not conserve energy, momentum, angular momentum, helicity, or vorticity, even though the physics of the Navier-Stokes equations dictate that they should. We aim in this work to construct discrete f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
122
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 35 publications
2
122
0
1
Order By: Relevance
“…For this reason, we call the '2D(u)u + (div u)u' formulation of the nonlinearity the EMAC formulation (energy, momentum, angular momentum conserving). In most common Galerkin methods for incompressible flow problems, such as mixed finite element methods, the divergence constraint is only enforced weakly [9], and in [4] we show how this is the main cause of conservation law violation if standard formulations of the nonlinearity are used. However, with the EMAC formulation, all of these conservation laws are obeyed in Galerkin discretizations.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…For this reason, we call the '2D(u)u + (div u)u' formulation of the nonlinearity the EMAC formulation (energy, momentum, angular momentum conserving). In most common Galerkin methods for incompressible flow problems, such as mixed finite element methods, the divergence constraint is only enforced weakly [9], and in [4] we show how this is the main cause of conservation law violation if standard formulations of the nonlinearity are used. However, with the EMAC formulation, all of these conservation laws are obeyed in Galerkin discretizations.…”
Section: Introductionmentioning
confidence: 86%
“…In the recent work [4], the authors showed that if the NSE system was discretized by a Galerkin method using the reformulation u · ∇u + ∇p = 2D(u)u + (div u)u + ∇P, with P = p − 1 2 |u| 2 and D denoting the rate of deformation tensor, then each of energy, momentum, angular-momentum, 2D enstrophy, helicity, and total vorticity would all be correctly balanced, even if the method does not enforce the divergence constraint strongly. For this reason, we call the '2D(u)u + (div u)u' formulation of the nonlinearity the EMAC formulation (energy, momentum, angular momentum conserving).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear term has been written in its convective form, which is most commonly encountered in computational practice. In the following, we consider the energy, momentum, and angular momentum conserving form for this term described in detail in NLemacfalse(boldufalse)=2boldu·bold-italicεfalse(boldufalse)+()·bolduboldu12false|boldufalse|2. …”
Section: Numerical Treatmentmentioning
confidence: 99%
“…The last term of Equation was absorbed in the pressure in the work of Charnyi et al by redefining the pressure as p=p12false|boldufalse|2, which has no physical meaning. Here, it is explicitly included in the formulation, avoiding the implementation of nonphysical Neumann conditions at outflow boundaries.…”
Section: Numerical Treatmentmentioning
confidence: 99%